The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1248/bpb.30.1702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ganoderma lucidum Polysaccharide on CYP2E1, CYP1A2 and CYP3A Activities in BCG-Immune Hepatic Injury in Rats

Abstract: Ganoderma lucidum (LEYSS, ex FR., G. lucidum) KARST has been prescribed to improve health and longevity in the traditional Chinese medicine, and it was used for the treatment of neurasthenia, hypertension, hepatopathy and carcinoma for thousands of years.1) More than one hundred species of bioactive components have been isolated from G. lucidum,2) such as polysaccharides, triterpenoids and alkaloids, in which that Ganoderma lucidum polysaccharide (GLPS) is one of the major active components. Its multiple pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
2
16
0
2
Order By: Relevance
“…As previously demonstrated, polysaccharides isolated from G. lucidum , induced total P450 levels in rat liver, whereas suppressed the activity of CYP1A2, CYP3A and CYP2E1 in hepatic microsomes [41]. Our results indicate that GLT is able to induce XRE/AhR and PXR which regulate expression of CYP1A2 and CYP3A, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…As previously demonstrated, polysaccharides isolated from G. lucidum , induced total P450 levels in rat liver, whereas suppressed the activity of CYP1A2, CYP3A and CYP2E1 in hepatic microsomes [41]. Our results indicate that GLT is able to induce XRE/AhR and PXR which regulate expression of CYP1A2 and CYP3A, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Sporocarps were cut into small pieces, dried at 40–50 °C for 48 h and powdered. Gl-PS were extracted by method of Wang et al with slight modification [36]. Briefly, Gl-PS was extracted by hot water from the ganoderma lucidum fruiting body, followed by ethanol precipitation, dialysis, and protein depletion using the Sevag method.…”
Section: Methodsmentioning
confidence: 99%
“…(Lingzhi), one of the most popular medicinal fungi with a long history in oriental countries, has been extensively used in the treatment of a variety of diseases including cancer, hyperlipidemia, diabetes, neurasthenia, insomnia, hypertension and chronic hepatopathy [10,11]. Ganoderma lucidum polysaccharide (Gl-PS), a glycopeptide isolated from the water-soluble polysaccharides of Ganoderma lucidum, is the primary effective component of Ganoderma lucidum [12][13][14]. Our and some others' previous studies have demonstrated that Gl-PS administration significantly prevented the progression of diabetic renal complications and attenuated myocardial collagen cross-linking and AGEs in diabetic rats, by exerting greater antioxidative activity [15,16].…”
Section: Introductionmentioning
confidence: 99%